2021
DOI: 10.3389/fnbeh.2021.786358
|View full text |Cite
|
Sign up to set email alerts
|

Delay Discounting in Established and Proposed Behavioral Addictions: A Systematic Review and Meta-Analysis

Abstract: Steep delay discounting, or a greater preference for smaller-immediate rewards over larger-delayed rewards, is a common phenomenon across a range of substance use and psychiatric disorders. Non-substance behavioral addictions (e.g., gambling disorder, internet gaming disorder, food addiction) are of increasing interest in delay discounting research. Individual studies have reported steeper discounting in people exhibiting various behavioral addictions compared to controls or significant correlations between di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 116 publications
0
24
0
Order By: Relevance
“…In line with this argument, individuals with impulsive disorders and addiction show steeper discounting of future rewards such as monetary gains [for overviews see (12)(13)(14)(15)]. Moreover, steeper discounting does not only differentiate between addiction disorders and healthy individuals, but it also predicts entry into drug use as well as therapy outcome (16,17), and has accordingly been described as a behavioral biomarker of addiction and its treatment (18).…”
Section: Introductionmentioning
confidence: 97%
“…In line with this argument, individuals with impulsive disorders and addiction show steeper discounting of future rewards such as monetary gains [for overviews see (12)(13)(14)(15)]. Moreover, steeper discounting does not only differentiate between addiction disorders and healthy individuals, but it also predicts entry into drug use as well as therapy outcome (16,17), and has accordingly been described as a behavioral biomarker of addiction and its treatment (18).…”
Section: Introductionmentioning
confidence: 97%
“…These studies have generally suggested a small relationship between delay discounting and FA [22,[52][53][54][55]. In addition, a recent meta-analysis suggested aggregate correlations between FA and steeper discounting were significant but small in magnitude (r = 0.12) [56]. This is in contrast to a meta-analysis that concluded a robust association between delayed reward discounting across many addictive substances [46].…”
Section: Delay Discountingmentioning
confidence: 88%
“…Several studies have found higher discount rates in patients with GD than healthy controls [ 15 , 19 , 20 , 21 , 22 , 23 ]. Moreover, there is evidence of an association between the severity of GD symptoms and high discount rates [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%